A history of conversion to Islam in the United States. Vol. 2. The African American Islamic Renaissance, 1920-1975 - Bowen, Patrick D. (Muslim Minorities, 2017)
In A History of Conversion to Islam in the United States, Volume 2: The African American Islamic Renaissance, 1920-1975 Patrick D. Bowen offers an in-depth account of African American Islam as it developed in the United States during the fifty-five years that followed World War I. Having been shaped by a wide variety of intellectual and social influences, the 'African American Islamic Renaissance' appears here as a movement that was characterized by both great complexity and diversity. Drawing from a wide variety of sources-including dozens of FBI files, rare books and periodicals, little-known archives and interviews, and even folktale collections-Patrick D. Bowen disentangles the myriad social and religious factors that produced this unprecedented period of religious transformation.